Pengaruh Kinerja Lingkungan pada Nilai Perusahaan dengan Good Corporate Governance Sebagai Variabel Pemoderasi - Edi Wijaya Kusuma, I Made; Dewi, Luh Gede Krisna (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p19, 2019)
The sample was taken by 35 companies with 5 years observation year so that the sample number was 175, using purposive sampling technique. The analysis technique used is Moderated Regression Analysis (RMA). Based on the results of the analysis it was found that environmental performance had a significant effect on the value of the company. This shows that the better or better the environmental performance of the company will be able to attract investors to invest because it has gained trust from the community so that this can increase the value of the company. And Good Corporate Governance, which is proxied as an Independent Board of Commissioners, can strengthen the influence of Environmental Performance on Corporate Values ??because the higher the proportion of independent commissioners, the more rigorous monitoring by independent board of commissioners in improving company performance. So that this can increase the value of the company. Keywords: Environmental performance, company value, good corporate governance